Analasis Penyebaran Kasus Perceraian Di Provinsi-Provinsi Indonesia Menggunakan Algoritma K-Mean - Yosep Nuryaman (INFORMATIKA SAINS TEKNOLOGI, 2025)
Technological developments do not always have a positive impact on various groups of society, including children, adults and the elderly. One of the things that has a negative impact is the increase in divorce due to easy internet access for non-positive activities such as online gambling and cheating. According to data received from the Central Statistics Agency, there have been 408,347 divorce cases spread across 39 provinces. This research was conducted to determine the distribution of divorce cases using the k-mean algorithm. From the research that has been carried out, divorce cases can be divided into 4 clusters with each cluster numbering 20 provinces, 3 provinces, 5 provinces and 6 provinces. The results of evaluating centroid proximity are -17122790.208